Party Savers - Mooney, E. S; Illustrated by Art Ruiz (U.S.A Scholastic, 2001)
"The Girls ... throw a come-as-your favorite-villain costume party--and the real villains decide to crash! Now it's Girls vs. villains in their own backyard!"
Including color illustration
Keywords: Powerpuff Girls (Fictitious characters) -- Girls